2021
DOI: 10.20471/acc.2021.60.04.08
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism and Serum Calcium in Breast Cancer Patients Evaluated for Low Bone Mass – A Single Center Experience

Abstract: SUMMARY The bone health guidelines for breast cancer (BC) patients recommend bone mineral density (BMD) testing. Patients with low BMD and elevated serum calcium levels (SCLs) are further evaluated for primary hyperparathyroidism (PHPT). We aimed to determine the prevalence of PHPT in treated BC patients with low BMD and analyze the association of SCLs with histopathologic tumor features and cancer treatment. This retrospective study included postmenopausal BC patients examined at Osteoporosis Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
3
0
0
Order By: Relevance
“…According to published literature, the possible cause of PHTP in patients with breast cancer could be prior neck or breast irradiation. 15,16 Our findings are in line with Punda et al demonstrated various sides of PTA whereas, Woll et al showed strong correlation between the side of breast radiation therapy with the side of PTA occurrence. 15,16 Bones are the most frequent site of breast cancer distant metastases and bone loss is frequently seen in patients under tamoxifen therapy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…According to published literature, the possible cause of PHTP in patients with breast cancer could be prior neck or breast irradiation. 15,16 Our findings are in line with Punda et al demonstrated various sides of PTA whereas, Woll et al showed strong correlation between the side of breast radiation therapy with the side of PTA occurrence. 15,16 Bones are the most frequent site of breast cancer distant metastases and bone loss is frequently seen in patients under tamoxifen therapy.…”
Section: Discussionsupporting
confidence: 90%
“…15,16 Our findings are in line with Punda et al demonstrated various sides of PTA whereas, Woll et al showed strong correlation between the side of breast radiation therapy with the side of PTA occurrence. 15,16 Bones are the most frequent site of breast cancer distant metastases and bone loss is frequently seen in patients under tamoxifen therapy. 10,17 Therefore, detection of the bone loss in such patients is usually considered as disease-related, whereas secondary causes of osteolytic lesions receive low attention.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation